2014
DOI: 10.1002/prs.11664
|View full text |Cite
|
Sign up to set email alerts
|

Incident investigation in Pakistan's fertilizer industry—Common safety management system failures and issues

Abstract: The learning from operational incidents plays a key role in improving the performance and safety of the chemical process plants. In this article, the incidents occurred during January 2011 to April 2012 in different sections, that is, Ammonia, Urea, and Utility Units of fertilizer sector in Pakistan have been analyzed using Why Tree analysis. The aim is to identify the failures in the safety management system to prevent the incidents. One thousand and fifteen, root and contributing causes identified in investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Rashid et al has shown that its very important to construct why tree diagrams for occurred accidents to identify the safety management systems failure. 21 Improvement in these safety management systems will prevent future incidents and enhance operational discipline. First step to construct a why tree diagram is to complete a detailed incident report form.…”
Section: Incident Investigation and Constructing Why Tree Diagrammentioning
confidence: 99%
See 2 more Smart Citations
“…Rashid et al has shown that its very important to construct why tree diagrams for occurred accidents to identify the safety management systems failure. 21 Improvement in these safety management systems will prevent future incidents and enhance operational discipline. First step to construct a why tree diagram is to complete a detailed incident report form.…”
Section: Incident Investigation and Constructing Why Tree Diagrammentioning
confidence: 99%
“…It was observed that flaws in operating procedures were responsible as a root or contributing cause for 13% of the occurred accidents or incidents. 21 Existence of work instructions improve operational discipline as they enlist step wise procedure for routine jobs and chance of errors minimize. Pre start-up safety review must be performed before the start-up of the normal facility or before the start-up of a newly installed facility or part of the facility.…”
Section: Existence Of Work Instructions or Operating Procedures And Pre Start-up Safety Reviews (Pssr)mentioning
confidence: 99%
See 1 more Smart Citation
“…11 Exactly 16% of the root or contributing causes for accidents in fertilizer complexes were due to deficiencies in PHA. 12 It is recommended that PHA can identify such causes and prevent accidents, 5 whereas the deficiencies in process safety of process plants can be highlighted via leading and lagging matrices. 13,14 PHA is one of the 14 elements of process safety management (PSM), 15 and metrics for PHA have been developed to monitor its performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the year 1991, the ammonia was released from Urea Fertilizer Factory Limited (UFFL), Bangladesh and led to severe damage including control room and also led to economic crises in the industry . Also in the year 2011, the ammonia was leaked from mechanical seal of ammonia feed pump in an ammonia storage facility located in Pakistan and this ammonia dispersed to the atmosphere . An operator was narrowly escaped from being affected by ammonia.…”
Section: Introductionmentioning
confidence: 99%